Fin Ray® Effect Inspired Soft Robotic Gripper: From the RoboSoft Grand Challenge toward Optimization - Crooks, Whitney; Vukasin, Gabrielle; O’Sullivan, Maeve; Messner, William; Rogers, Chris (Frontiers in Robotics and AI, 2016)
A soft robotic gripper for a Tele-operable In-Home Robotic Assistant (TIHRA) for the mobility impaired is presented. This gripper is inspired by the Fin Ray® Effect, which is derived from the physiology of fish fins. The gripper “fingers” are soft and triangular with hard crossbeams that buckle and deform in to conform around objects. The fingers of the TIHRA were altered from the original Fin Ray® design in order to create a preferred bending direction, resulting in less force required to obtain a good grip on an object. The entire gripper can be 3D printed as part of a soft robotic hand made from hard and soft materials, and the motor-tendon actuation system attaches in a limited number of steps. Testing of the gripper included modeling the fingers and comparing grip strength them to the original Fin Ray® to verify their optimization. Models show that the TIHRA fingers deform 15% more than traditional fingers when subjected to the same force. The TIHRA gripper was capable of holding 560 g, approximately 40% more than the gripper equipped with traditional fingers. This difference was statistically significant (p $\ll$ 0.001). The TIHRA hand was also tested at the 2016 RoboSoft Grand Challenge in Livorno, Italy. The gripper successfully completed some tasks, highlighting its conformability, deformability, and morphology, but performed poorly in others, demonstrating the need to increase the gripper strength to prevent out of plane twisting and bending and to increase the force that the gripper can exert. The gripper was attached to a Baxter robot to demonstrate its ability to interface with existing technology, and other versions of the gripper were designed and manufactured to show the scalability and versatility of the design.